Lesotho Water Security and Climate Change Assessment - World Bank Group (World Bank, Washington, DC, 2016)
The analysis looks specifically at the need to ensure continued development of water resources within Lesotho and aims to empower stakeholders to act with more confidence by demonstrating that the implementation strategies can provide benefits to water resources management over a broad range of possible future scenarios. The analysis quantifies a range of possible future conditions to demonstrate the benefits that can be realized over a broad range of possible future outcomes. This quantification is based on a water resource decision support model developed specifically for Lesotho, using the Water Evaluation and Planning (WEAP) model which couples climate, hydrologic, and water management systems to facilitate an evaluation of the uncertainties and strategies of impacts on specified management metrics. The WEAP model was used to simulate the historic climate based on data from the national government archives and global datasets available in the public domain. These included 121 downscaled Global Climate Model (GCM) projections of future climate over two possible water demand future scenarios, for a total of 244 scenarios up to the year 2050.